Enantiomerically pure amines as substrates for the Ti‐catalyzed hydroamination of alkynes - Pohlki, Frauke; Doye, Sven (European journal of organic chemistry, 2004)
Abstract: For two representative reactions employing enantiomerically pure (S)?1?phenylethylamine and (S)-1-cyclohexylethylamine it is shown that Ti-catalyzed hydroamination reactions of alkynes do not generally take place without partial racemization at the chiral center adjacent to the nitrogen atom. However, identified from a selection of nine Ti catalysts, Cp*2TiMe2 and at least two other catalysts can be used for racemization-free hydroamination reactions of alkynes. Furthermore, the amount of racemization can be reduced significantly by the addition of pyridine to the reaction mixture.